Management of Internal Root Resorption #x2013; A Case Series (Global Journal of Medical Research, 2020)
There is always a dilemma of whether to treat a tooth with a questionable prognosis endodontic ally or extract it and subsequently place an implant. Management of a case of internal root resorption is a challenge to the endodontists. Internal resorption of teeth is an insidious process and is generally found in teeth with previous history of trauma. It may occur in cases with chronicpulpal inflammation, following caries or due to trauma in the form of an accidental blow.This case series report a different method for the management of internal root resorption which showed a favorable prognosis due to appropriate choice of endodontic treatment followed by prosthesis.
Keywords: endodontic treatment; internal root resorption; calcium hydroxide thermoplastized gutapercha technique; MTA GJMR-J Classification: NLM